PENGARUH PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION DENGAN MEDIA RODA PINTAR PECAHAN TERHADAP HASIL BELAJAR SISWA KELAS IV SDN LABUY - Luthfia, Zulfa; Hayati , Zikra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in elementary school often faces challenges, particularly in helping students understand abstract concepts such as fractions. Therefore, appropriate learning approaches and instructional media are needed to support students’ understanding. This study aims to determine whether there is an effect of the implementation of the Realistic Mathematics Education (RME) approach assisted by the smart fraction wheel media on students’ mathematics learning outcomes on fraction material. This study used a quantitative approach with a quasi-experimental method and a control group pretest–posttest design. The research subjects consisted of two classes, namely the experimental class that applied the RME approach with the smart fraction wheel media and the control class that used conventional learning. Data were collected through students’ learning outcome tests and analyzed using normality tests, homogeneity tests, and the independent samples t-test. The results showed that the significance value obtained from the independent samples t-test was 0.000 < 0.05. This indicates that there is an effect of the implementation of the Realistic Mathematics Education approach assisted by the smart fraction wheel media on students’ learning outcomes. The average posttest score of the experimental class was higher than that of the control class, namely 86.80 and 74.50. Therefore, it can be concluded that there is an effect of the implementation of the Realistic Mathematics Education approach assisted by the smart fraction wheel media on students’ mathematics learning outcomes in fraction material. Keywords: Realistic Mathematics Education, smart fraction wheel media, learning outcomes, fractions, elementary school.